Pola Pengasuhan Ayah Terhadap Kemampuan Fisik Motorik Dan Sosial Emosional Pada Anak Usia Dini - Mei Ariani Kusumawati; Rachma Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out how many fathers are involved in caring for early childhood children in the Surabaya area. The background of this research is to look at the phenomenon of fathers' lack of involvement in child care, resulting in some children behaving in fear, lacking self-confidence, speaking harshly, and not being able to control their emotions. This research is a quantitative descriptive research with a survey method. The subjects of this research were fathers who had young children in the Surabaya sub-district area. Respondents in this study totaled 332 fathers. The research results show that as many as 84% ​​of fathers have high involvement in their children's care in Surabaya Village. However, based on the data, 42% of fathers are still busy with their activities when they are with their children and as many as 46% of fathers are still not close to their children, such as kissing and hugging their children. Therefore, it is necessary to provide training to fathers on how to care for early childhood children which includes aspects: Interaction, giving an example, accompanying, supervising, providing warmth and meeting the child's needs.